Association between hemodynamic conditions and occlusion times after flow diversion in cerebral aneurysms. (2nd April 2014) - Mut, Fernando; Raschi, Marcelo; Scrivano, Esteban; Bleise, Carlos; Chudyk, Jorge; Ceratto, Rosana; Lylyk, Pedro; Cebral, Juan R
Abstract : Background: Evaluation of flow diversion treatment of intracranial aneurysms is difficult owing to lack of knowledge of the target hemodynamic environment. Objective: To identify hemodynamic conditions created after flow diversion that induce fast aneurysm occlusion. Methods: Two groups of aneurysms treated with flow diverters alone were selected: (a) aneurysms completely occluded at 3 months (fast occlusion), and (b) aneurysms patent or incompletely occluded at 6 months (slow occlusion). A total of 23 aneurysms were included in the study. Patient-specific computational fluid dynamics models were constructed and used to characterize the hemodynamic environment immediately before and after treatment. Average post-treatment hemodynamic conditions between the fast and slow occlusion groups were statistically compared. Results: Aneurysms in the fast occlusion group had significantly lower post-treatment mean velocity (fast=1.13cm/s, slow=3.11cm/s, p=0.02), inflow rate (fast=0.47mL/s, slow=1.89mL/s, p=0.004) and shear rate (fast=20.52 1/s, slow=32.37 1/s, p=0.02) than aneurysms in the slow occlusion group. Receiver operating characteristics analysis showed that mean post-treatment velocity, inflow rate, and shear rate below a certain threshold could discriminate between aneurysms of the fast and slow occlusion groups with good accuracy (84%, 77%, and 76%, respectively). Conclusions: The occlusion time of cerebral aneurysms treated with flow diverters can be predicted by the hemodynamic conditions created immediately after device implantation. Specifically, low post-implantation flow velocity, inflow rate, and shear rate are associated with fast occlusion times.